Influence of the emotionally positive attitude on forming the communicative competences of technology teachers - Hevko, I. V. (Journal of Education, Health and Sport, 2017)
The article reveals the influence of an emotionally positive attitude on the formation of communicative competences of technology teachers. In the article under communicative competence, the author considers the quality of a person characterized by certain properties, in particular by properties that necessary for perceptual activity, personal-communicative and communicative-operational activities. It is proved that the creation of an emotionally positive mood in the learning environment acts as one of the factors of pedagogical stimulation in our study and the formation of the communicative competence of the future specialist in the technological profile.